Pengaruh Pupuk Kompos Lamtorogung (Leucaena leucocephala) dan Jarak Tanam Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Lycopersicum esculentum Mill.) - Mardhiah Hayati; Erita Hayati; Khairi Narossa (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
The Effect of Lamtorogung Manure (Leucaena leucocephala) and Planting Spacing on Growth and Yield of Tomatoes (Lycopersicum esculentum Mill.)ABSTRACT. The aim of this study was to find out the effect of dosages of lamtorogung manure and planting spacing, and interaction between them, on both growth and yield of tomatoes. Treatments were arranged by Factorial Completely Randomized Block Design 3 x 3 with 3 replications. Factors evaluated were dosage of lamtorogung manure (15, 25 and 35 ton ha-1) and planting spacing (50 cm x 60 cm, 50 cm x 70 cm and 50 cm x 80 cm). Variables observed were the height of plant and diameter of the lower end of stem at 15, 30 and 45 days after planting, the number of fruits per plant (3 times harvest), the weight of fruits per plant, and diameter of fruit. The result of the study indicated that dosage of lamtorogung manure of 25 ton ha-1 was the best for the highest tomato yield, and planting spacing of 50 cm x 80 cm was the best for both plants growth and yield. There was no interaction between both treatments towards growth and yield.